The Influence of Leadership Style, and Work Culture on Employee Performance Mediated by Motivation at PT Permodalan Nasional Madani Mekaar Region Pati 2 - Setyawan, Ade Cresna; Jahja, Adi Susilo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to look at how Leadership gaya dan lingkungan kerja mempengaruhi motivasi pekerja. at PNM Mekaar Regional Pati 2. Data was collected through surveys distributed to Mekaar karyawan dan wawancara langsung dengan manajer Mekaar. Hypotheses were tested using partial least squares (PLS) using a sample of 89 people. The study found that leadership style and work culture have a positive impact on job motivation; leadership style and work culture have a positive impact on employee performance, but work culture has little impact on performance. However, leadership style and work culture have a positive impact on employee performance by motivating them; work motivation can moderate the relationship between leadership style and work culture